Analisis Perbandingan Load Balancing Menggunakan Algoritma Round Robin dan Weighted Round Robin pada Mikrotik - Muhammad Lailul Karim; Muhammad Imron Rosadi (Sekawan Institut, 2026)
This study analyzes and compares the performance of Round Robin (RR) and Weighted Round Robin (WRR) load balancing algorithms in a multi-WAN network environment using MikroTik devices. The research aims to evaluate the effectiveness of both algorithms in distributing network traffic across internet links with unequal bandwidth capacities. The experimental setup consisted of two ISP connections with bandwidths of 10 Mbps and 20 Mbps, configured on a MikroTik RB750Gr3 router. Performance evaluation was conducted using key network parameters, in-cluding packet loss, Latency, bandwidth utilization, and CPU load. The results show that the Round Robin algorithm, which distributes traffic evenly without considering link capacity, leads to high packet loss and unstable Latency, particularly on the lower-bandwidth link. In contrast, the Weighted Round Robin algorithm, which allocates traffic proportionally based on bandwidth capacity using a 1:2 ratio, demonstrates significantly better performance. WRR reduces packet loss by up to 4–6 times, provides more stable Latency, optimizes bandwidth utilization, and re-sults in lower CPU load on the router. Although WRR requires more complex configuration, the findings indicate that it is more suitable and efficient for multi-WAN networks with significant bandwidth differences between ISP links.